Recent competition in the Japanese life insurance industry - Toshiyuki Souma; Yoshiro Tsutsui (Osaka University, Institute of Social and Economic Research (ISER), 2005)
This paper examines a change in the level of competition in the Japanese life insurance industry over the last 17 years. We estimate the first order condition for profit-maximizing insurance oligopolies to obtain the degree of non-competition and collusion. Estimation results suggest that: 1) not only stock companies, but also mutual companies maximize their own profits rather than pay out dividends to policyholders; 2) competition has become stronger since 1995; 3) revision of Insurance Industry Law and failures of insurance companies promoted the competition; and 4) the competition in the recent years is still more lax than the pre-war period.
Keywords: G22; L13; L21; 330; Life insurance; Degree of competition; Collusion; Japan